2012
DOI: 10.1002/cphc.201100962
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nascent Rotational Energy Distributions and Reaction Mechanisms of the Gas‐Phase Radical–Radical Reaction O(3P)+(CH3)2CH→C3H6+OH

Abstract: This paper reports on the gas-phase radical-radical dynamics of the reaction of ground-state atomic oxygen [O((3)P), from the photodissociation of NO(2)] with secondary isopropyl radicals [(CH(3))(2)CH, from the supersonic flash pyrolysis of isopropyl bromide]. The major reaction channel, O((3)P)+(CH(3))(2)CH→C(3)H(6) (propene)+OH, is examined by high-resolution laser-induced fluorescence spectroscopy in crossed-beam configuration. Population analysis shows bimodal nascent rotational distributions of OH (X(2)Π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The result also shows good agreement with the other theoretical investigations of the reverse reaction of C 2 H 2 + OH, where as the OH radical approaches C 2 H 2 , the association complex exists as the prereaction association complex along the entrance channel . Similar weakly bound adducts were reported in the authors’ studies on the formation of OH in the reactions of O­( 3 P) with ethyl and iso -propyl radicals. , …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The result also shows good agreement with the other theoretical investigations of the reverse reaction of C 2 H 2 + OH, where as the OH radical approaches C 2 H 2 , the association complex exists as the prereaction association complex along the entrance channel . Similar weakly bound adducts were reported in the authors’ studies on the formation of OH in the reactions of O­( 3 P) with ethyl and iso -propyl radicals. , …”
Section: Resultssupporting
confidence: 90%
“…This investigation was carried out as part of continuing efforts to deduce the general principles that explain the mechanistic and dynamic traits of atom-radical reactions. In recent years, the authors have reported gas-phase crossed-beam studies of the reaction dynamics of O­( 3 P) with saturated hydrocarbon radicals such as methyl (CH 3 ), ethyl (C 2 H 5 ), and t -butyl ( t -C 4 H 9 ) and unsaturated π-conjugated hydrocarbon radicals such as allyl (C 3 H 5 ) and propargyl (C 3 H 3 ). A supersonic flash pyrolysis source was adopted to produce clean, jet-cooled radical beams without experiencing recombination and/or secondary dissociation. By means of ab initio simulations and statistical calculations, these experiments revealed that the atom-radical reactions followed microscopic mechanisms with unusual dynamic features.…”
Section: Introductionmentioning
confidence: 99%
“…The newly formed OH in the ν = 0 level has a rotational temperature parameter of 6000 K while the OH remaining from the parent water molecule has a T r of 2600 K. Both temperature parameters depend on the vibrational level. The chemical reactions which produce OH from hydrocarbons have been shown to be able to yield rotational distributions of the OH(X), which can be described by the superposition of two Boltzmann distributions [90,91]. Similar studies have been performed for other molecules, such as NH(X) [92], HD [93] and NaH [94] which originate from dissociation reactions.…”
Section: Chemical and Neutral Induced Dissociation Reactionsmentioning
confidence: 75%
“…The lab-made crossed-beam machine utilized in this study has been described in detail elsewhere. [3][4][5][6][7][8][9][10][11] Briefly, the machine consisted of two source chambers, each outfitted with a 6-inch baffled diffusion pump, and a scattering chamber equipped with a 10-inch baffled diffusion pump. O( 3 P) was generated by irradiating He samples seeded with 12% NO 2 with a pulsed laser with a wavelength of 355 nm.…”
Section: Experiments and Ab Initio Calculationsmentioning
confidence: 99%
“…This work develops from this lab's recent progress in crossed-beam investigations of the reaction dynamics of O( 3 P) with a series of prototypical hydrocarbon radicals such as allyl (C 3 H 5 ), propargyl (C 3 H 3 ), t-butyl (t-C 4 H 9 ), ethyl (C 2 H 5 ) and iso-propyl (i-C 3 H 7 ). [4][5][6][7][8][9][10][11] All alkyl radicals were produced using a supersonic flash pyrolysis developed by Chen and coworkers. 12 The labile precursor molecules entrained in a molecular beam experienced a very short residence time inside a high-temperature tube, leading to rapid thermal decomposition into clean, jet-cooled radical beams without recombination and/or secondary dissociation.…”
Section: Introductionmentioning
confidence: 99%